Development Trend of Global Design Patent Research - Chen, Rain (Recent Patents on Engineering, 2015)
Although nearly all previous studies in the patent domain are focused on invention patents, design patents have also become more and more important because of the continuous escalating and record-breaking compensation for design patent infringement. In fact, over the past few years, the number of Design Patent Research (DPR) has increased substantially. In this study, the investigators explored the development trend of DPR by thoroughly reviewing the three major periodical index databases in the world, and they are (1) Social Science Citation Index (SSCI), (2) Science Citation Index (SCI) and (3) Engineering Index (EI). The investigators also analyzed the samples in three stages. The study results showed the development trend of global design patent research between 1998 and 2013 (for a total of 16 years). The study provides future DPR with critical reference.
Keywords: design patents